Postprandial cardiorespiratory responses and the regulation of digestion-associated tachycardia in Nile tilapia (Oreochromis niloticus) - Guagnoni, Igor Noll [UNESP]; Armelin, Vinicius Araújo [UNESP]; da Silva Braga, Victor Hugo [UNESP]; Rantin, Francisco Tadeu; Florindo, Luiz Henrique [UNESP] (Springer Nature, 2021)
Cardiorespiratory adjustments that occur after feeding are essential to supply the demands of digestion in vertebrates. The well-documented postprandial tachycardia is triggered by an increase in adrenergic activity and by non-adrenergic non-cholinergic (NANC) factors in mammals and crocodilians, while it is linked to a withdrawal of vagal drive and NANC factors in non-crocodilian ectotherms—except for fish, in which the sole investigation available indicated no participation of NANC factors. On the other hand, postprandial ventilatory adjustments vary widely among air-breathing vertebrates, with different species exhibiting hyperventilation, hypoventilation, or even no changes at all. Regarding fish, which live in an environment with low oxygen capacitance that requires great ventilatory effort for oxygen uptake, data on the ventilatory consequences of feeding are also scarce. Thus, the present study sought to investigate the postprandial cardiorespiratory adjustments and the mediation of digestion-associated tachycardia in the unimodal water-breathing teleost Oreochromis niloticus. Heart rate (fH), cardiac autonomic tones, ventilation rate (fV), ventilation amplitude, total ventilation and fH/fV variability were assessed both in fasting and digesting animals under untreated condition, as well as after muscarinic cholinergic blockade with atropine and double autonomic blockade with atropine and propranolol. The results revealed that digestion was associated with marked tachycardia in O. niloticus, determined by a reduction in cardiac parasympathetic activity and by circulating NANC factors—the first time such positive chronotropes were detected in digesting fish. Unexpectedly, postprandial ventilatory alterations were not observed, although digestion triggered mechanisms that were presumed to increase oxygen uptake, such as cardiorespiratory synchrony.
Keywords: Autonomic nervous system; Cardiorespiratory adjustments; Digestion; Postprandial tachycardia; Specific dynamic action